Archaeology and palaeo-speleology at the cave Zala - Boschian, Giovanni (Array, 2010)
The cave Zala is situated North-east of Ogulin (Gorski kotar, Croatia), in a karstic area developed on Lower Cretaceous limestones. It belongs to a complex underground system, whose most important entrances are the Đulin ponor - Medvedica cave system and the Gojak spring cave ; at present, the cave is acting as a secondary spring connected to the Bistrac stream, which flows few hundred meters far from the cave. Archaeological excavations have been carried out by the Department of Archaeology, Faculty of Humanities and Social Sciences, University of Zagreb (prog. Ivor Karavanić) in the outer part of the cave, a small dry chamber connected to the inner system by a short passage. The excavations have put into light traces of human frequentation that span from the Late Upper Palaeolithic to the Middle Ages indicating a long and recurring-though apparently discontinuous-use of the cave for the shelter. It appears that archaeological data and composition and quantity of finds indicate many short-term occupation episodes during various archaeological periods. Beside abovementioned periods, traces of human activity from periods of late Antiquity, late Bronze Age and Mesolitic were also documented. In Bronze Age and Mesolithic layers traces of several hearts were found. Other levels contained only finds of fragmented pottery of lithics and animal bones. The geoarchaological aspects of the clastic infilling of the cave are at present under examination, mostly through sedimentological and soil micromorphological studies. The preliminary results of the these studies are providing interesting information about the palaeoclimatic conditions that caracterised the area durin the phases of human frequentation ; these were extremly cold during the late phases of the Late Glacial and the beginning of the Holocene, and were probably enhanced by local topographic effects. It can also be shown that the outer part of the cave was connected to the inside by a much wider passage, so that it was periodically flooded by the river flowing from the inside of the underground system. This may partly explain the gaops in the cultural sequence, which was partly eroded by flow ; moreover, some hints about the discharge capacity of the system in the past may be inferred from the sedimentological data.